Envisioning Industry 4.0 to 5.0: the Brazilian glass workplace - Ribeiro, Vagner Batista [UNESP]; Melo, Julio Cesar [UNESP]; Muniz Jr, Jorge [UNESP]; de Souza, Fernando Bernardi [UNESP]; Canever, Renato Cardoso [UNESP] (Emerald, 2024)
Purpose: This paper aims to investigate the impacts of Industry 4.0/5.0 (I4.0/5.0) on the glass manufacturing workplace. Specifically, it studied the workplace, which represents complex manufacturing lines of high variety and volume of products. Design/methodology/approach: A case study based on semi-structured interviews was conducted with managers responsible for I4.0 implementation, and the responses were treated by content analysis. Findings: Findings reinforce I5.0 aspects to be considered in terms of work organization. The interviewees highlight work and human factors as important for technology implementation, which includes workers tasks, skills, nature of work, human resources development, hiring process and organizations strategies. It was also found that knowledge sharing poses a huge challenge. Originality/value: In lieu of gaps in the literature, this research further discusses management challenges to support digital transformation and impacts on workers and organizations.
Keywords: Brazil; Glass industry; Industry 4.0; Industry 5.0; Knowledge; Worker; Workplace learning